Population structure and activity pattern of one species of Adenoma Steindachner, 1867 (Anura: Leptodactylidae) in northeastern Brazil - Maria Juliana Borges-Leite (Acta Herpetologica, 2016)
We analyzed the population structure and sexual size dimorphism of an Adenomera species occurring in the municipality of São Gonçalo do Amarante, from September 2010 to August 2011, using pitfall traps and active searches. We captured 116 individuals; 36 males, 23 females and 57 juveniles. Sexual size dimorphism was not observed. The smallest individuals were found in the middle of the rainy season, and the higher abundance of juveniles during this period may be related to recruitment. Females were captured in pitfall traps more often than males, while males were captured during active searches more often than females due to their calling behavior. We provide basic information regarding this Adenomera population, located in a region of severe environmental degradation, which may serve as a source of information for future studies of the area aiming to evaluate how the construction of industrial complexes affects anuran populations.